Porous multi-metallic Pt-based nanostructures as efficient electrocatalysts for ethanol oxidation: A mini-review - Adewale K. Ipadeola (12699590) (2022)
Porous multi-metallic Pt-based nanostructures (PM-Pt-Ns) electrocatalysts possess various unique structural and compositional merits that facilitate their utilization in ethanol oxidation reaction (EOR), which is one of the most important parameters in ethanol-based fuel cells. Improving the EOR activity of PM-Pt-Ns electrocatalysts with low Pt-content remains a daunting challenge, so various efforts devoted to overcoming these barriers lie in controlling nanoparticle shapes/compositions using a variety of methods. This mini-review evaluates the most interesting papers related to PM-Pt-Ns (i.e., binary and ternary) electrocatalysts for EOR with annotations in the last three years. Different preparation methods, morphologies and compositions of PM-Pt-Ns electrocatalysts on the EOR activity are discussed, as well as the challenges for scalable fabrication of PM-Pt-Ns electrocatalysts as anodes for practical ethanol-based fuel cells. Finally, the prospects for directing the development of novel PM-Pt-Ns for practical applications are emphasized. Other Information Published in: Electrochemistry Communications License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.elecom.2022.107330